Real Money Investors and Sovereign Bond Yields - Jaramillo, Laura (IMF Working Papers; Working Paper ;, 2013)
Experience from the global financial crisis suggests that countries' borrowing costs are not solely determined by macro and fiscal fundamentals. Factors such as ownership structures of government securities, among others, also play a significant role. This paper investigates the effect of 'real money investors'-domestic nonbanks and national and foreign central banks-on bond yields for a sample of 45 advanced and emerging market economies. The results show that, while bond yields rise with the debt to GDP ratio, this increase is partly offset if this debt falls in the hands of real money investors. Nonetheless, for some countries there is the risk that such ownership structure could change over the long run, which would impose upward pressure on borrowing costs, especially where fiscal positions are weak.